FE analysis of the effects of simplifications in experimental testing on micromotions of uncemented femoral knee implants. Issue 5 (18th December 2015) - Berahmani, Sanaz; Janssen, Dennis; Wolfson, David; de Waal Malefijt, Maarten; Fitzpatrick, Clare K.; Rullkoetter, Paul J.; Verdonschot, Nico
ABSTRACT: Experimental testing of orthopaedic implants requires simplifications concerning load application and activities being analyzed. This computational study investigated how these simplifications affect micromotions at the bone‐implant interface of an uncemented femoral knee implant. As a basis, validated in vivo loads of the stance phase of gait and a deep knee bend were adopted. Eventually, three configurations were considered: (i) simulation of the complete loading cycle; (ii) inclusion of only tibiofemoral loads (ignoring patellofemoral loads); and (iii) applying only a single peak tibiofemoral force. For all loading conditions the largest micromotions found at the proximal anterior flange. Without the patellofemoral force, peak micromotions increased 6% and 22% for gait and deep knee bend, respectively. By applying a single peak tibiofemoral force micromotions were overestimated. However, the peak micromotions corresponded to the maximum tibiofemoral force, and strong micromotion correlations were found between a complete loading cycle and a single peak load ( R 2 = 0.73 and R 2 = 0.89 for gait and deep knee bend, respectively). Deep knee bend resulted in larger micromotions than gait. Our study suggests that a simplified peak force can be used to assess the stability of cementless femoral components. For more robust testing, implants should be subjected to different loading modes. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:812–819, 2016.